The isolated resonance method for investigating orientation effects and electron energy losses of hyperchanneled particles - Shershnev, V.M.; Skakun, N.A. (Вопросы атомной науки и техники, 2005)
The isolated resonance of the nuclear reaction on impurity interstitials was used to investigate orientation effects. The method is shown to provide the best energy resolution in comparison with other methods. The ¹³C(p,γ) ¹⁴N reaction resonance at a proton energy of 1.7476 MeV was used to investigate the proton flux distribution in the (0001) plane channel of the single-crystal solution Re-0.4 at.%¹³C. Some special features of the γ-quantum yield of the reaction in relation to energy have been established. Electron energy losses of hyperchanneled protons were measured. It is demonstrated that the γ-quantum yield of the channeled proton-excited reaction is dependent on the amplitude of thermal vibrations of carbon atoms. Ізольований резонанс ядерної реакції на впроваджених атомах домішок використано для вивчення орієнтаційних ефектів. Показано, що цей метод дозволяє одержати краще енергетичне розрізнення у порів- нянні з іншими методами. Резонанс реакції ¹³C(p,γ) ¹⁴N, при енергії протонів 1,7476 МеВ, використовувався для дослідження розподілу потоку протонів у площинному каналі (0001) монокристалічного розчину Re- 0,4 ат.%¹³С. Встановлено особливості виходу γ-квантів реакції в залежності від енергії. Виміряно електронні втрати енергії гіперканальованих протонів. Показано, що вихід γ-квантів реакції, що збуджується канальованими протонами, залежить від амплітуди теплових коливань атомів вуглецю. Изолированный резонанс ядерной реакции на примесных атомах внедрения использован для изучения ориентационных эффектов. Показано, что этот метод позволяет получить лучшее энергетическое разрешение по сравнению с другими методами. Резонанс реакции ¹³C(p,γ) ¹⁴N, при энергии протонов 1,7476 МэВ, использовался для исследования распределения потока протонов в плоскостном канале (0001) монокристаллического раствора Re-0,4 ат.%¹³С. Установлены особенности выхода γ-квантов реакции в зависимости от энергии. Измерены электронные потери энергии гиперканалированных протонов. Показано, что выход γ- квантов реакции, возбуждаемой каналированными протонами, зависит от амплитуды тепловых колебаний атомов углерода.